Mortality in Joubert syndrome. Issue 5 (28th March 2017) - Dempsey, Jennifer C.; Phelps, Ian G.; Bachmann‐Gagescu, Ruxandra; Glass, Ian A.; Tully, Hannah M.; Doherty, Dan
Abstract : Joubert syndrome (JS) is a rare, recessively inherited neurodevelopmental disorder characterized by a distinctive mid‐hindbrain malformation. Little is known about mortality in affected individuals. Identifying the timing and causes of death will allow for development of healthcare guidelines for families and providers and, thus, help to prolong and improve the lives of patients with JS. We evaluated information on 40 deceased individuals with JS to characterize age and cause of death. We compared this population with 525 living individuals with JS to estimate associations between risk of death and extra‐neurological features. Genetic causes were examined in both groups. Mean age of death in this cohort was 7.2 years, and the most prevalent causes of death were respiratory failure (35%), particularly in individuals younger than 6 years, and kidney failure (37.5%), which was more common in older individuals. We identified possible associations between risk of death and kidney disease, liver fibrosis, polydactyly, occipital encephalocele, and genetic cause. This work highlights factors (genetic cause, extra‐neurological organ involvement, and other malformations) likely to be associated with higher risk of mortality in JS, which should prompt increased monitoring for respiratory issues, kidney disease, and liver fibrosis.